Joyce, Ulysses and Postcolonialism - Ehsan Emami Neyshaburi (Journal of Humanistic and Social Studies, 2021)
Postcolonialism speaks of those people, who have been militarily, politically, and perforce culturally subjected to another nation. This branch of criticism is worth practicing because it plays a very important role at least in the lives of the oppressed all over the world by providing them with pain relief; a pain that still continues to gnaw away at the souls of a large colonized population. Although at the mention of post colonialism most people think of African and Caribbean countries and of black people, this paper signifies that the first and oldest British colony had been Ireland; that exploitation does not make a distinction between black and white. This paper is going to find traces of anti colonialism or decolonization in Joyce’s Ulysses and to show that how using the colonizer’s language, the Irish novelist implicitly writes back to the empire and what extent Joyce’s personality has been under the influence of post colonialism. The paper also reiterates that although Joyce regarded Irish Nationalism and Irish Literary Revival as useless and failing, he never surrendered to the language and culture imposed by the colonizer.